Handbook of research on human-computer interfaces and new modes of interactivity - Blashki, Kathy, 1961-; Isaias, Pedro (Engineering Science Reference, an imprint of IGI Global, 2020)
"This book explores and discusses innovative studies of technology and its application in the implementation of interactivity in interface design and development (through Web 1.0 to 3.0) and welcomes significant research in human-computer interfaces and interaction"--